EVALUASI KESESUAIAN PERESEPAN OBAT DIARE ANAK BERDASARKAN MANAJEMEN TERPADU BALITA SAKIT KEMENKES 2022 DI KLINIK “X” KABUPATEN SIDOARJO - Andito, Didik; Sulistyowati, Emi; Priyoherianto, Andri; Puspadina, Valiandri (Fakultas Farmasi UMI, 2025)
Diarrhea is an incident of defecation with a consistency that is more liquid than usual, with a frequency of three or more times per day. Improper and rapid management is the main cause of death from diarrhea. The Ministry of Health has begun to disseminate the Guidelines for the Management of Sick Toddler Therapy (MTBS) 2022. This study aims to evaluate the suitability of prescribing children's diarrhea medications by the Ministry of Health MTBS 2022 guidelines in the outpatient unit of Clinic